2017
DOI: 10.3390/life7020015
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Condensation of Glycine and Alanine on Metal Ferrite Surface: Primitive Peptide Bond Formation Scenario

Abstract: The amino acid condensation reaction on a heterogeneous mineral surface has been regarded as one of the important pathways for peptide bond formation. Keeping this in view, we have studied the oligomerization of the simple amino acids, glycine and alanine, on nickel ferrite (NiFe2O4), cobalt ferrite (CoFe2O4), copper ferrite (CuFe2O4), zinc ferrite (ZnFe2O4), and manganese ferrite (MnFe2O4) nanoparticles surfaces, in the temperature range from 50–120 °C for 1–35 days, without applying any wetting/drying cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 66 publications
2
20
0
Order By: Relevance
“…We mention the idea of prebiotic hydrothermal compartments to explain a scenario under which a SP can be validated. In this scenario, each compartment acts as an individual sub-reaction chamber producing molecules in yields similar to those reported by other investigators [24,25]. However, in this scenario these compartments release the products of their reaction, either via destruction of the compartment or through leaky walls.…”
Section: Testability Of Scientific Models Of Lifesupporting
confidence: 67%
See 1 more Smart Citation
“…We mention the idea of prebiotic hydrothermal compartments to explain a scenario under which a SP can be validated. In this scenario, each compartment acts as an individual sub-reaction chamber producing molecules in yields similar to those reported by other investigators [24,25]. However, in this scenario these compartments release the products of their reaction, either via destruction of the compartment or through leaky walls.…”
Section: Testability Of Scientific Models Of Lifesupporting
confidence: 67%
“…MFT suggests that the chemistry leading to life could have occurred in a relatively stable environment containing some catalytic activities that would have expedited the production of other important and relevant bio-molecules. Many proponents of MFT believe minerals served several critical functions during this process [24,25]. These functions include: catalysis, protection, support and selection.…”
Section: Two Competing Empirical Theories About the Origin Of Lifementioning
confidence: 99%
“…In the origin of life point of view, amino acid touches on the surface of inorganic materials at the deep sea near the hydrothermal vent and the effect of the inorganics on the stability of amino acid has been studied. It was reported that iron compounds enhance dimerization to form alanyl-alanine and diketopiperazine at hydrothermal condition [53]. Glycine and alanine are reacted at 100°C for 35 days with metal ferrites such as NiFeO 4 to obtain 30% of yield of dimerization products [53].…”
Section: Previous Studies On Solid Catalytic Reaction Of Amino Acid Imentioning
confidence: 99%
“…It was reported that iron compounds enhance dimerization to form alanyl-alanine and diketopiperazine at hydrothermal condition [53]. Glycine and alanine are reacted at 100°C for 35 days with metal ferrites such as NiFeO 4 to obtain 30% of yield of dimerization products [53].…”
Section: Previous Studies On Solid Catalytic Reaction Of Amino Acid Imentioning
confidence: 99%
“…He floats the idea that such nitrogenous bases of purine and pyrimidine can be made on Earth, on the surface of iron oxide nano-particles, namely NiFe 2 O 4 , CoFe 2 O 4 , CuFe 2 O 4 , ZnFe 2 O 4 and MnFe 2 O 4 as these divalent metal ions in iron oxide make them excellent catalytic systems. These minerals may have been present on Earth by 300 million years after its formation [4,24,25]. Konstantinos Papasakellariou (Agricultural University of Athens) delivered an impressive oral presentation on a high throughput computational approach for the fractionation of RNA species from whole transcriptomes.…”
Section: Genetics Firstmentioning
confidence: 99%